Higher dose antiviral therapy for herpes infections is associated with a risk of serious adverse events in older adults with chronic kidney disease - Patricia Olar; Amit X. Garg; Matthew A. Weir; Fatemeh Ahmadi; Eric McArthur; Ngan N. Lam; Jessica M. Sontrop; Flory T. Muanda (Pharmacology Research & Perspectives)
Abstract Antiviral use has been linked to encephalopathy and elevated serum creatinine concentrations in individuals with chronic kidney disease (CKD) in case reports. Using linked healthcare data in Ontario, we conducted a population‐based cohort study on adults aged ≥66 years not receiving dialysis and newly prescribed oral acyclovir, valacyclovir, or famciclovir in the outpatient setting (2008–2022) at higher versus lower doses. The primary composite outcome, a hospital visit with encephalopathy or acute kidney injury (AKI) within 14 days of initiating antiviral treatment, was examined in a primary cohort. AKI was assessed in a secondary cohort of older adults with CKD with available linked hospital‐based laboratory (lab) data. We used inverse probability of treatment weighting on the propensity score to balance comparison groups on baseline health. Weighted risk ratios (RR) and risk differences (RD) were obtained using modified Poisson and binomial regression. In the primary cohort, higher‐ versus lower‐dose antiviral was not associated with an increased 14‐day risk of hospital visit with encephalopathy or AKI. However, Higher‐ versus lower‐dose antiviral was associated with a higher risk of a hospital visit with AKI when assessed using lab values (weighted number of events, 70 of 8407 [0.83%] versus 18 of 8230 [0.22%], respectively; weighted RR, 3.83 [95% CI, 1.87–7.87]; weighted RD, 0.62% [95% CI, 0.37%–0.86%]). In older adults with CKD, starting an antiviral at a higher versus lower dose was associated with a higher risk of AKI, although the absolute risk of this event was <1%.